2015
DOI: 10.1128/aac.00992-15
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal Activity of ME1111, a New Topical Agent for Onychomycosis, against Clinical Isolates of Dermatophytes

Abstract: The treatment of onychomycosis has improved considerably over the past several decades following the introduction of the oral antifungals terbinafine and itraconazole. However, these oral agents suffer from certain disadvantages, including drug interactions and potential liver toxicity. Thus, there is a need for new topical agents that are effective against onychomycosis. ME1111 is a novel selective inhibitor of succinate dehydrogenase (complex II) of dermatophyte species, whose small molecular weight enhances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…ME1111 demonstrated antifungal activity as potent as that of ciclopirox against clinical dermatophyte strains isolated from Japanese patients, including T. rubrum and T. mentagrophytes, which are common etiologic agents of onychomycosis (Table 1). These results are in line with the activity of ME1111 against clinical dermatophyte isolates obtained from patients in the United States (18), where the MIC 90 against the U.S. isolates was 0.25 mg/liter. The finding that the susceptibility of dermatophyte isolates obtained from the U.S. sites to ME1111 was similar to that of isolates from non-U.S. sites indicates that there is no difference 8% ciclopirox lacquer (Penlac) 6 0.00 Ϯ 0.00 5% amorolfine lacquer (Loceryl) 6 0.00 Ϯ 0.00 in ME1111 susceptibility among the dermatophyte species obtained worldwide.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…ME1111 demonstrated antifungal activity as potent as that of ciclopirox against clinical dermatophyte strains isolated from Japanese patients, including T. rubrum and T. mentagrophytes, which are common etiologic agents of onychomycosis (Table 1). These results are in line with the activity of ME1111 against clinical dermatophyte isolates obtained from patients in the United States (18), where the MIC 90 against the U.S. isolates was 0.25 mg/liter. The finding that the susceptibility of dermatophyte isolates obtained from the U.S. sites to ME1111 was similar to that of isolates from non-U.S. sites indicates that there is no difference 8% ciclopirox lacquer (Penlac) 6 0.00 Ϯ 0.00 5% amorolfine lacquer (Loceryl) 6 0.00 Ϯ 0.00 in ME1111 susceptibility among the dermatophyte species obtained worldwide.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, it was reported that the MICs of ME1111 against 7 strains of terbinafine-resistant T. rubrum were not elevated (18). Our study also demonstrated the potent activity of ME1111 against a terbinafine-resistant T. mentagrophytes strain.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It is highly active in vitro and in vivo against Trichophyton rubrum and Trichophyton mentagrophytes and shows excellent human nail permeability (1)(2)(3)(4). A previous study on its mechanism of action revealed that the molecular target of ME1111 was succinate dehydrogenase (complex II) in the mitochondrial electron transport system (5).…”
mentioning
confidence: 99%
“…Fig. 1) is a new agent discovered by Meiji Seika Pharma Co., Ltd. (Tokyo, Japan), that possesses potent in vitro antifungal activity against dermatophytes, such as Trichophyton rubrum and Trichophyton mentagrophytes, which are common causative organisms of onychomycosis (14,15). A small molecular weight is reported to be one of the important factors of a compound for nail penetration ability (16).…”
mentioning
confidence: 99%